Method for producing solid electrolyte

By combining Li3PS4 with composite agent 1 and composite agent 2 to form a composite, the problem that solid electrolytes in the liquid phase method is difficult to achieve high ionic conductivity, and efficient and uniform electrolyte preparation is achieved, which significantly improves the conductivity of the electrolyte.

JP7667146B2Active Publication Date: 2025-04-22IDEMITSU KOSAN CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022522174
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-26
Filing Date
2021-05-12
Publication Date
2025-04-22
Estimated Expiration
2041-05-12

AI Technical Summary

Technical Problem

The existing liquid phase methods are difficult to achieve high ionic conductivity in solid electrolytes, mainly due to partial decomposition or defects in the electrolyte during precipitation.

Method used

By combining Li3PS4 with composite agent 1 and composite agent 2, a composite compound is formed. Using the different characteristics of composite agent 1 and composite agent 2, the reaction is promoted and the uniform dispersion state of raw materials is maintained, thereby obtaining crystal electrolytes with high ionic conductivity.

Benefits of technology

It is possible to efficiently obtain a solid electrolyte with high ionic conductivity in the liquid phase method, avoiding the decomposition and defect problems of the electrolyte during the precipitation process, and significantly improving the conductive properties of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667146000005
    Figure 0007667146000005
  • Figure 0007667146000006
    Figure 0007667146000006
  • Figure 0007667146000007
    Figure 0007667146000007
Patent Text Reader

Abstract

Provided is a solid electrolyte production method through which a solid electrolyte having high ion conductivity is obtained using the liquid-phase method, said production method being characterized by including a first step for mixing two or more types of compounds which satisfy (1) and a complexing agent 1 which satisfies (2) with one another, and a second step for also mixing in a complexing agent 2 which satisfies (3) after the first step. (1) A compound which contains one or more types selected from the group consisting of elemental lithium, elemental sulfur, elemental phosphorus and elemental halogen. (2) A complexing agent which is capable of forming a complex and contains Li3PS4 and elemental halogen. (3) A complexing agent which is not complexing agent 1, is capable of forming a complex, and contains Li3PS4.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a solid electrolyte. [Background technology]

[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras, and mobile phones, the development of batteries to be used as power sources for these devices has become important. Conventionally, electrolytes containing flammable organic solvents have been used in batteries used for such purposes, but by making the battery fully solid-state, flammable organic solvents are not used in the battery, safety devices can be simplified, and manufacturing costs and productivity are excellent, so that batteries in which the electrolyte is replaced with a solid electrolyte layer are being developed.

[0003] The manufacturing methods of the solid electrolyte used in the solid electrolyte layer are roughly divided into a solid-phase method and a liquid-phase method. The liquid-phase method is further divided into a homogeneous method in which the solid electrolyte material is completely dissolved in a solvent, and a heterogeneous method in which the solid electrolyte material is not completely dissolved and goes through a solid-liquid coexistence suspension. For example, as a solid-phase method, a method is known in which raw materials such as lithium sulfide and diphosphorus pentasulfide are subjected to mechanical milling treatment using a device such as a ball mill or a bead mill, and then heated as necessary to produce an amorphous or crystalline solid electrolyte (see, for example, Patent Document 1). According to this method, a solid electrolyte is obtained by applying mechanical stress to raw materials such as lithium sulfide to promote a reaction between solids. On the other hand, as a homogeneous liquid phase method, a method in which a solid electrolyte is dissolved in a solvent and reprecipitated is known (see, for example, Patent Document 2), and as a heterogeneous method, a method in which a solid electrolyte raw material such as lithium sulfide is reacted in a solvent containing a polar aprotic solvent is known (see Patent Documents 3 and 4, and Non-Patent Document 1). For example, Patent Document 4 discloses a method for producing a solid electrolyte with a Li4PS4I structure, which includes a step of using dimethoxyethane (DME) and combining it with a Li3PS4 structure to obtain Li3PS4·DME. The ionic conductivity of the obtained solid electrolyte is 5.5×10 -5 S / cm (Calcium doped: 3.9 × 10-4 In recent years, the liquid phase method has been attracting attention as a method that can be easily and mass-produced in addition to its versatility and applicability in order to commercialize all-solid-state batteries. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2017 / 159667 Brochure [Patent Document 2] JP 2014-191899 A [Patent Document 3] International Publication No. 2014 / 192309 Brochure [Patent Document 4] International Publication No. 2018 / 054709 Brochure [Non-patent literature]

[0005] [Non-Patent Document 1] “CHEMISTRY OF MATERIALS”, 2017, No. 29, pp. 1830-1835 Summary of the Invention [Problem to be solved by the invention]

[0006] However, conventional solid-phase methods involving mechanical milling and other processes are centered on solid-phase reactions, and are able to achieve high ionic conductivity because they make it easy to obtain a solid electrolyte with high purity. In contrast, liquid-phase methods dissolve the solid electrolyte, which can cause decomposition or loss of some of the solid electrolyte components during precipitation, making it more difficult to achieve high ionic conductivity than solid-phase synthesis methods. For example, in the homogeneous method, the raw materials and solid electrolyte are completely dissolved once, so that the components can be uniformly dispersed in the liquid. However, in the subsequent precipitation process, precipitation proceeds according to the solubility specific to each component, so it is extremely difficult to maintain the dispersion state of the components while precipitating. As a result, each component separates and precipitates. In addition, in the homogeneous method, the affinity between the solvent and lithium becomes too strong, so the solvent is difficult to remove even when dried after precipitation. For these reasons, the homogeneous method has the problem that the ionic conductivity of the solid electrolyte is significantly reduced. In the heterogeneous solid-liquid coexistence method, a part of the solid electrolyte is dissolved, and separation occurs due to elution of a specific component, making it difficult to obtain a desired solid electrolyte.

[0007] The present invention has been made in view of the above circumstances, and has an object to provide a production method for efficiently obtaining a solid electrolyte having high ionic conductivity using a liquid phase method. [Means for solving the problem]

[0008] As a result of intensive research aimed at solving the above problems, the present inventors have discovered the following and have completed the present invention. 1. When the raw materials for a solid electrolyte, Li2S, P2S5, etc., are mixed in the presence of a complexing agent 1 that has the ability to form Li3PS4 and can form a complex containing the formed Li3PS4 and a halogen element, Li3PS4 is formed, and further, a complex containing the formed Li3PS4 and a halogen element is formed, and the dispersion state of the various raw materials is maintained uniformly. Therefore, even after the precipitation process, a precursor for a solid electrolyte in which each main component is uniformly dispersed can be obtained, and ultimately a crystalline solid electrolyte with high lithium ion conductivity can be obtained. 2. The reaction of forming Li3PS4 using complexing agent 1 stagnates after proceeding to a certain extent. 3. After initiating the reaction with complexing agent 1, by further adding complexing agent 2, which has a superior Li3PS4 formation rate compared to complexing agent 1, the Li3PS4 formation reaction, which would stagnate with complexing agent 1 alone, proceeds without stagnation. That is, it has been found that the above problem can be solved by the following invention.

[0009] [1] A method for producing a solid electrolyte, comprising: a first step of mixing two or more compounds satisfying the following (1) and a complexing agent 1 satisfying the following (2); and, after the first step, a second step of further mixing a complexing agent 2 satisfying the following (3). (1) A compound containing one or more elements selected from the group consisting of lithium, sulfur, phosphorus and halogen elements. (2) A complexing agent capable of forming a complex containing Li3PS4 and a halogen element. (3) A complexing agent other than complexing agent 1 capable of forming a complex containing Li3PS4. [2] The method for producing a solid electrolyte according to the above [1], wherein the complexing agent 1 contains a nitrogen element. [3] The method for producing a solid electrolyte according to the above [1] or [2], wherein the complexing agent 2 contains an oxygen element. [4] The method for producing a solid electrolyte according to any one of the above [1] to [3], wherein the complexing agent 1 has two or more amino groups. [5] The method for producing a solid electrolyte according to any one of the above [1] to [4], wherein the complexing agent 2 has one or more groups selected from the group consisting of an ether group and an ester group. [6] The method for producing a solid electrolyte according to any one of the above [1] to [5], wherein the complexing agent 1 is tetramethylethylenediamine. [7] The method for producing a solid electrolyte according to any one of the above [1] to [6], wherein the complexing agent 2 is tetrahydrofuran. [8] The method for producing a solid electrolyte according to any one of the above [1] to [6], wherein the complexing agent 2 is dimethoxyethane. [9] The method for producing a solid electrolyte according to any one of the above [1] to [8], wherein a molar ratio of the amount of complexing agent 1 added to the total molar amount of Li atoms contained in two or more of the compounds satisfying the above (1) is 0.1 or more and 2.0 or less.

[10] A method for producing a solid electrolyte according to any one of [1] to [9] above, wherein the molar ratio of the amount of complexing agent 2 added to the total molar amount of Li3PS4 that can be produced from two or more compounds satisfying (1) above is 1.0 or more and 5.0 or less.

[11] The method for producing a solid electrolyte according to any one of the above [1] to

[10] , wherein the compound satisfying the above (1) includes a lithium halide.

[12] The method for producing a solid electrolyte according to any one of the above [1] to

[11] , wherein the compound satisfying the above (1) contains an elemental halogen.

[13] The method for producing a solid electrolyte according to any one of the above [1] to

[12] , wherein the halogen element is a bromine element or an iodine element.

[14] The method for producing a solid electrolyte according to any one of the above [1] to

[13] , wherein the compound satisfying the above (1) includes lithium sulfide and diphosphorus pentasulfide.

[15] The method for producing a solid electrolyte according to any one of the above [1] to

[14] , wherein the compound satisfying the above (1) includes Li3PS4.

[16] The method for producing a solid electrolyte according to any one of the above [1] to

[15] , wherein no pulverization and mixing is carried out in the first step.

[17] The method for producing a solid electrolyte according to any one of the above [1] to

[16] , wherein the solid electrolyte contains a thiolicon region II type crystal structure.

[18] The method for producing a solid electrolyte according to any one of the above [1] to

[17] , wherein the solid electrolyte does not have diffraction peaks at 2θ=17.5° and 26.1° in X-ray diffraction measurement using CuKα radiation. Effect of the Invention

[0010] According to the present invention, it is possible to provide a production method for efficiently obtaining a solid electrolyte having high ionic conductivity by using a liquid phase method. [Brief description of the drawings]

[0011] [Figure 1] 1 shows X-ray diffraction spectra of an electrolyte precursor, an amorphous solid electrolyte, and a crystalline solid electrolyte obtained in Example 1. [Diagram 2] 1 shows X-ray diffraction spectra of raw materials used in Examples and Comparative Examples. [Diagram 3] 1 is an X-ray diffraction spectrum of the solid electrolyte obtained in Example 2. [Figure 4] 1 is an X-ray diffraction spectrum of the solid electrolyte obtained in Example 4. [Diagram 5] 1 is an X-ray diffraction spectrum of the solid electrolyte obtained in Example 5. [Figure 6] 1 is an X-ray diffraction spectrum of the solid electrolyte obtained in Comparative Example 5. [Figure 7] 1 shows infrared absorption spectra measured by FT-IR analysis (diffuse reflectance method) of the complexes obtained in Production Examples 2 and 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention (hereinafter, sometimes referred to as "the present embodiment") will be described. In this specification, the upper and lower limit values ​​of the numerical ranges of "greater than or equal to", "less than or equal to", and "to" are values ​​that can be combined arbitrarily, and the numerical values ​​of the examples can also be used as the upper and lower limit values. Furthermore, provisions that are considered to be preferable can be adopted arbitrarily. In other words, one provision that is considered to be preferable can be adopted in combination with one or more other provisions that are considered to be preferable. It can be said that a combination of preferable things is more preferable.

[0013] The method for producing a solid electrolyte of the present embodiment is characterized by including a first step of mixing two or more compounds satisfying the following (1) and a complexing agent 1 satisfying the following (2), and a second step of further mixing, after the first step, a complexing agent 2 satisfying the following (3). (1) A compound containing one or more elements selected from the group consisting of lithium, sulfur, phosphorus and halogen elements. (2) A complexing agent capable of forming a complex containing Li3PS4 and a halogen element. (3) A complexing agent other than complexing agent 1 capable of forming a complex containing Li3PS4.

[0014] [Solid electrolyte] In this specification, the term "solid electrolyte" refers to an electrolyte that maintains a solid state under a nitrogen atmosphere at 25° C. The solid electrolyte in this embodiment is a solid electrolyte that contains lithium, sulfur, phosphorus, and halogen elements and has ionic conductivity due to the lithium element.

[0015] The term "solid electrolyte" includes both a crystalline solid electrolyte having a crystal structure obtained by the manufacturing method of this embodiment and an amorphous solid electrolyte. In this specification, the crystalline solid electrolyte is a solid electrolyte in which a peak derived from the solid electrolyte is observed in the X-ray diffraction pattern in the X-ray diffraction measurement, and it does not matter whether or not there is a peak derived from the raw material of the solid electrolyte. That is, the crystalline solid electrolyte includes a crystal structure derived from the solid electrolyte, and a part of the crystal structure may be derived from the solid electrolyte, or the whole of the crystal structure may be derived from the solid electrolyte. And, as long as the crystalline solid electrolyte has the above-mentioned X-ray diffraction pattern, it may include an amorphous solid electrolyte in a part of it. Therefore, the crystalline solid electrolyte includes so-called glass ceramics obtained by heating an amorphous solid electrolyte to a crystallization temperature or higher. In this specification, the term "amorphous solid electrolyte" refers to an amorphous solid electrolyte that has a halo pattern in which no peaks other than those derived from the material are substantially observed in an X-ray diffraction pattern obtained by X-ray diffraction measurement, regardless of whether or not there are peaks derived from the raw materials of the solid electrolyte.

[0016] [Compounds that satisfy (1)] The compound (hereinafter, also simply referred to as "raw material") used in this embodiment that satisfies (1) is a compound containing one or more elements selected from the group consisting of lithium element, sulfur element, phosphorus element, and halogen element, and two or more of such compounds are used. More specifically, lithium sulfide; lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide; phosphorus sulfides such as diphosphorus trisulfide (P2S3) and diphosphorus pentasulfide (P2S5); phosphorus halides such as various phosphorus fluorides (PF3, PF5), various phosphorus chlorides (PCl3, PCl5, P2Cl4), various phosphorus bromides (PBr3, PBr5), and various phosphorus iodides (PI3, P2I4); thiophosphoryl fluoride (PSF3), thiophosphoryl chloride (P Representative examples of the raw material include raw materials consisting of at least two elements selected from the above four elements, such as thiophosphoryl halides, such as thiophosphoryl bromide (PSBr3), thiophosphoryl iodide (PSI3), thiophosphoryl fluoride dichloride (PSCl2F), and thiophosphoryl fluoride dibromide (PSBr2F); and elemental halogens, such as fluorine (F2), chlorine (Cl2), bromine (Br2), and iodine (I2), with bromine (Br2) and iodine (I2) being preferred.

[0017] Examples of the other raw materials that can be used include raw materials containing at least one element selected from the above four elements and containing an element other than the four elements, more specifically, lithium compounds such as lithium oxide, lithium hydroxide, and lithium carbonate; alkali metal sulfides such as sodium sulfide, potassium sulfide, rubidium sulfide, and cesium sulfide; metal sulfides such as silicon sulfide, germanium sulfide, boron sulfide, gallium sulfide, tin sulfide (SnS, SnS2), aluminum sulfide, and zinc sulfide; phosphate compounds such as sodium phosphate and lithium phosphate; halides of alkali metals other than lithium, such as sodium iodide, sodium fluoride, sodium chloride, and sodium bromide; metal halides such as aluminum halides, silicon halides, germanium halides, arsenic halides, selenium halides, tin halides, antimony halides, tellurium halides, and bismuth halides; and phosphorus oxyhalides such as phosphorus oxychloride (POCl3) and phosphorus oxybromide (POBr3).

[0018] Among the above, lithium sulfide, phosphorus sulfide such as diphosphorus trisulfide (P2S3) and diphosphorus pentasulfide (P2S5), halogen elements such as fluorine (F2), chlorine (Cl2), bromine (Br2), and iodine (I2), and lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide are preferred. In addition, when oxygen element is introduced into the solid electrolyte, phosphoric acid compounds such as lithium oxide, lithium hydroxide, and lithium phosphate are preferred. As a combination of raw materials, for example, a combination of lithium sulfide, diphosphorus pentasulfide, and lithium halide, and a combination of lithium sulfide, diphosphorus pentasulfide, and halogen elements are preferred, and lithium halide is preferably lithium bromide or lithium iodide, and halogen elements are preferably bromine and iodine.

[0019] In this embodiment, Li3PS4 containing the PS4 structure can be used as a part of the raw material. Specifically, Li3PS4 is prepared in advance by manufacturing or the like, and used as the raw material. The content of Li3PS4 in the total of the raw materials is preferably 60 to 100 mol%, more preferably 65 to 90 mol%, and further preferably 70 to 80 mol%.

[0020] In addition, when Li3PS4 and a simple halogen are used, the content of the simple halogen relative to Li3PS4 is preferably 1 to 50 mol %, more preferably 10 to 40 mol %, even more preferably 20 to 30 mol %, and even more preferably 22 to 28 mol %.

[0021] The lithium sulfide used in this embodiment is preferably in the form of particles. The average particle size of lithium sulfide particles (D 50 In this specification, the average particle size (D 50) is the particle size at which the particle size distribution cumulative curve is accumulated from the smallest particle size to 50% of the total, and the volume distribution is the average particle size that can be measured using, for example, a laser diffraction / scattering particle size distribution measuring device. Among the above-mentioned examples of raw materials, the solid raw materials preferably have an average particle size similar to that of the lithium sulfide particles, that is, within the same range as the average particle size of the lithium sulfide particles.

[0022] When lithium sulfide, diphosphorus pentasulfide, and lithium halide are used as raw materials, the ratio of lithium sulfide to the total of lithium sulfide and diphosphorus pentasulfide is preferably 70 to 80 mol%, more preferably 72 to 78 mol%, and even more preferably 74 to 78 mol%, from the viewpoint of obtaining higher chemical stability and higher ionic conductivity. When lithium sulfide, diphosphorus pentasulfide, lithium halide, and other raw materials used as necessary are used, the content of lithium sulfide and diphosphorus pentasulfide relative to the total of these is preferably 60 to 100 mol%, more preferably 65 to 90 mol%, and even more preferably 70 to 80 mol%. Furthermore, when lithium bromide and lithium iodide are used in combination as the lithium halide, from the viewpoint of improving ion conductivity, the ratio of lithium bromide to the total of lithium bromide and lithium iodide is preferably 1 to 99 mol%, more preferably 20 to 90 mol%, even more preferably 40 to 80 mol%, and particularly preferably 50 to 70 mol%.

[0023] In the case where a halogen element is used as a raw material, and lithium sulfide and diphosphorus pentasulfide are used, the ratio of the number of moles of lithium sulfide excluding the same number of moles of lithium sulfide as the halogen element to the total number of moles of lithium sulfide and diphosphorus pentasulfide excluding the same number of moles of lithium sulfide as the halogen element is preferably within the range of 60 to 90%, more preferably within the range of 65 to 85%, even more preferably within the range of 68 to 82%, even more preferably within the range of 72 to 78%, and particularly preferably within the range of 73 to 77%. This is because higher ion conductivity can be obtained at these ratios. From the same viewpoint, when lithium sulfide, diphosphorus pentasulfide, and a halogen element are used, the content of the halogen element relative to the total amount of lithium sulfide, diphosphorus pentasulfide, and the halogen element is preferably 1 to 50 mol%, more preferably 2 to 40 mol%, even more preferably 3 to 25 mol%, and even more preferably 3 to 15 mol%.

[0024] When lithium sulfide, diphosphorus pentasulfide, a halogen element, and a lithium halide are used, the content of the halogen element (α mol %) and the content of the lithium halide (β mol %) relative to the total amount thereof preferably satisfy the following formula (2), more preferably satisfy the following formula (3), even more preferably satisfy the following formula (4), and even more preferably satisfy the following formula (5). 2≦2α+β≦100…(2) 4≦2α+β≦80 …(3) 6≦2α+β≦50 …(4) 6≦2α+β≦30 …(5)

[0025] When two types of halogens are used as simple substances, the molar number of one halogen element in the substance is A1 and the molar number of the other halogen element in the substance is A2, and A1:A2 is preferably 1 to 99:99 to 1, more preferably 10:90 to 90:10, even more preferably 20:80 to 80:20, and even more preferably 30:70 to 70:30.

[0026] Furthermore, when the two types of halogen elements are bromine and iodine, the molar number of bromine is B1 and the molar number of iodine is B2, then B1:B2 is preferably 1 to 99:99 to 1, more preferably 15:85 to 90:10, even more preferably 20:80 to 80:20, even more preferably 30:70 to 75:25, and particularly preferably 35:65 to 75:25.

[0027] [Complexing agent 1 that satisfies (2)] In this specification, the complexing agent 1 is a complexing agent that satisfies the above (2), i.e., is capable of forming a complex containing Li3PS4 and a halogen element obtained from Li2S and P2S5, etc., which are preferably used as raw materials for solid electrolytes, preferably has the ability to form Li3PS4, and is capable of forming a complex containing the formed Li3PS4 and a halogen element, and is used in the first step.

[0028] The complexing agent 1 can be used without any particular limitation as long as it has the above-mentioned properties, and is preferably a compound containing an element having a high affinity with lithium, such as a hetero element such as nitrogen, oxygen, or chlorine, and more preferably a compound having a group containing such a hetero element, because such a hetero element or group containing such a hetero element can be coordinated (bonded) with lithium.

[0029] The hetero element present in the molecule of the complexing agent 1 has a high affinity with the lithium element, and is considered to have the ability to easily form a complex by bonding with Li3PS4 containing the PS4 structure, which is the main skeleton of the solid electrolyte produced by this embodiment, and raw materials containing lithium and halogen elements such as lithium halide. Therefore, by mixing the above raw materials with the complexing agent 1, the complex is formed, and it becomes possible to precipitate various components while maintaining their dispersed state even in the precipitation process, and an electrolyte precursor in which the halogen element is more uniformly dispersed and fixed is obtained, and as a result, it is considered that a solid electrolyte with high ionic conductivity is obtained.

[0030] The ability of complexing agent 1 to form a complex containing Li3PS4 and a halogen element can be directly confirmed by the infrared absorption spectrum measured by FT-IR analysis (diffuse reflectance method) in the examples described later. In the examples, the powder obtained by stirring complexing agent 1 (tetramethylethylenediamine, hereinafter also simply referred to as "TMEDA") and lithium iodide (LiI), and complexing agent 1 itself were analyzed by FT-IR analysis (diffuse reflectance method). As shown in FIG. 7, the powder obtained by stirring complexing agent 1 and lithium iodide has a spectrum of TMEDA itself and a spectrum of 1000 to 1250 cm -1 It can be seen that the peaks derived from the CN stretching vibration in are different. In addition, it is known that the LiI-TMEDA complex is formed by stirring and mixing MEDA and lithium iodide (for example, Aust. J. Chem., 1988, 41, 1925-34, especially Fig. 2, etc.), so it is thought that the LiI-TMEDA complex is formed.

[0031] On the other hand, when the powder obtained by stirring the complexing agent 1 (tetramethylethylenediamine, TMEDA) and Li3PS4 was analyzed by FT-IR analysis (diffuse reflectance method) in the same manner as above, the spectrum of TMEDA itself was different from that of the powder in the 1000-1250 cm -1 The spectrum of the LiI-TMEDA complex is similar to that of the LiI-TMEDA complex, suggesting that the Li3PS4-TMEDA complex is formed. Thus, the above-mentioned condition (2) that the complexing agent 1 satisfies, that is, the property of being able to form a complex containing Li3PS4 and a halogen element, is a property that can be specifically confirmed.

[0032] Therefore, the complexing agent 1 preferably has at least two hetero elements capable of coordinating (bonding) in the molecule, and more preferably has a group containing at least two hetero elements in the molecule. By having a group containing at least two hetero elements in the molecule, it is possible to bond raw materials containing lithium and halogen, such as Li3PS4 and lithium halide, via at least two hetero elements in the molecule. Among the hetero elements, nitrogen is preferred, and the group containing nitrogen is preferably an amino group. In other words, the complexing agent is preferably an amine compound.

[0033] The amine compound is not particularly limited as long as it has an amino group in the molecule and can promote the formation of a complex, but a compound having at least two amino groups in the molecule is preferred. By having such a structure, Li3PS4 and raw materials containing lithium and halogen, such as lithium halide, can be bonded via at least two nitrogen elements in the molecule.

[0034] Examples of such amine compounds include aliphatic amines, alicyclic amines, heterocyclic amines, and aromatic amines, and these can be used alone or in combination of two or more kinds.

[0035] More specifically, representative and preferred examples of the aliphatic amine include aliphatic primary diamines such as ethylenediamine, diaminopropane, and diaminobutane; aliphatic secondary diamines such as N,N,N'-dimethylethylenediamine, N,N'-diethylethylenediamine, N,N'-dimethyldiaminopropane, and N,N'-diethyldiaminopropane; and aliphatic tertiary diamines such as N,N,N',N'-tetramethyldiaminomethane, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, N,N,N',N'-tetramethyldiaminopropane, N,N,N',N'-tetraethyldiaminopropane, N,N,N',N'-tetramethyldiaminobutane, N,N,N',N'-tetramethyldiaminopentane, and N,N,N',N'-tetramethyldiaminohexane. In the examples given in this specification, for example, in the case of diaminobutane, unless otherwise specified, all isomers are included, such as isomers relating to the position of the amino group, such as 1,2-diaminobutane, 1,3-diaminobutane, and 1,4-diaminobutane, as well as linear and branched isomers for butane.

[0036] The number of carbon atoms in the aliphatic amine is preferably 2 or more, more preferably 4 or more, and even more preferably 6 or more, with the upper limit being preferably 10 or less, more preferably 8 or less, and even more preferably 7 or less. The number of carbon atoms in the aliphatic hydrocarbon group in the aliphatic amine is preferably 2 or more, and the upper limit being preferably 6 or less, more preferably 4 or less, and even more preferably 3 or less.

[0037] Representative and preferred examples of the alicyclic amine include alicyclic primary diamines such as cyclopropanediamine and cyclohexanediamine; alicyclic secondary diamines such as bisaminomethylcyclohexane; and alicyclic tertiary diamines such as N,N,N',N'-tetramethyl-cyclohexanediamine and bis(ethylmethylamino)cyclohexane. Representative and preferred examples of the heterocyclic amine include heterocyclic primary diamines such as isophoronediamine; heterocyclic secondary diamines such as piperazine and dipiperidylpropane; and heterocyclic tertiary diamines such as N,N-dimethylpiperazine and bismethylpiperidylpropane. The number of carbon atoms in the alicyclic amine and heterocyclic amine is preferably 3 or more, more preferably 4 or more, and the upper limit is preferably 16 or less, more preferably 14 or less.

[0038] Representative and preferred examples of the aromatic amine include aromatic primary diamines such as phenyldiamine, tolylenediamine, and naphthalenediamine; aromatic secondary diamines such as N-methylphenylenediamine, N,N'-dimethylphenylenediamine, N,N'-bismethylphenylphenylenediamine, N,N'-dimethylnaphthalenediamine, and N-naphthylethylenediamine; and aromatic tertiary diamines such as N,N-dimethylphenylenediamine, N,N,N',N'-tetramethylphenylenediamine, N,N,N',N'-tetramethyldiaminodiphenylmethane, and N,N,N',N'-tetramethylnaphthalenediamine. The aromatic amine has preferably 6 or more, more preferably 7 or more, and even more preferably 8 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and even more preferably 12 or less.

[0039] The amine compound used in the present embodiment may be substituted with a substituent such as an alkyl group, an alkenyl group, an alkoxyl group, a hydroxyl group, or a cyano group, or with a halogen atom. Although diamines have been given as specific examples, it goes without saying that the amine compounds that can be used in this embodiment are not limited to diamines, and examples thereof include aliphatic monoamines corresponding to various diamines such as trimethylamine, triethylamine, ethyldimethylamine, and the above-mentioned aliphatic diamines, piperidine compounds such as piperidine, methylpiperidine, and tetramethylpiperidine, pyridine compounds such as pyridine and picoline, morpholine compounds such as morpholine, methylmorpholine, and thiomorpholine, imidazole compounds such as imidazole and methylimidazole, and the above-mentioned alicyclic diamines. In addition to monoamines such as alicyclic monoamines such as the corresponding monoamines, heterocyclic monoamines corresponding to the above heterocyclic diamines, and aromatic monoamines corresponding to the above aromatic diamines, polyamines having three or more amino groups, such as diethylenetriamine, N,N',N''-trimethyldiethylenetriamine, N,N,N',N'',N''-pentamethyldiethylenetriamine, triethylenetetramine, N,N'-bis[(dimethylamino)ethyl]-N,N'-dimethylethylenediamine, hexamethylenetetramine, and tetraethylenepentamine, can also be used.

[0040] Among the above, from the viewpoint of obtaining higher ion conductivity, a tertiary amine having a tertiary amino group as an amino group is preferable, a tertiary diamine having two tertiary amino groups is more preferable, a tertiary diamine having two tertiary amino groups at both ends is even more preferable, and an aliphatic tertiary diamine having a tertiary amino group at both ends is even more preferable. In the above amine compounds, the aliphatic tertiary diamine having a tertiary amino group at both ends is preferably tetramethylethylenediamine, tetraethylethylenediamine, tetramethyldiaminopropane, or tetraethyldiaminopropane, and considering the ease of availability, etc., tetramethylethylenediamine or tetramethyldiaminopropane is preferable.

[0041] Similar effects can also be obtained with compounds having a nitrogen atom as a heteroatom and a group other than an amino group, such as a nitro group or an amide group.

[0042] From the viewpoint of efficiently forming a complex, the molar ratio of the amount of complexing agent 1 added to the total molar amount of Li atoms contained in two or more compounds satisfying the above (1) is preferably 0.1 or more and 2.0 or less, more preferably 0.5 or more and 1.5 or less, even more preferably 0.8 or more and 1.2 or less, and most preferably 1.0.

[0043] [Complexing agent 2 satisfying (3)] In this specification, the complexing agent 2 is a complexing agent other than the complexing agent 1 that satisfies the above (3), i.e., is capable of forming a complex containing Li3PS4 obtained from Li2S and P2S5, which are preferably used as raw materials for solid electrolytes, and is used in the first step. In particular, it refers to a complexing agent that forms Li3PS4 at a faster rate than the complexing agent 1. By further mixing complexing agent 2 after mixing complexing agent 1, it is possible to allow the Li3PS4 formation reaction to proceed without stagnation, which would otherwise stagnate if only complexing agent 1 was mixed.

[0044] The reason why this is possible is unclear, but the following hypothesis is conceivable. That is, although complexing agent 1 has an excellent balance between the ability to form Li3PS4 and the ability to form a complex containing Li3PS4 and a halogen element, it is inferior to complexing agent 2 in its ability to form Li3PS4, so that the Li3PS4 formation reaction proceeds, and when the concentration of Li2S etc. present in the system decreases, the rate of the Li3PS4 formation reaction slows down and gradually stagnates. However, by further mixing complexing agent 2, which has a superior ability to form Li3PS4 compared to complexing agent 1, after mixing complexing agent 1, it becomes possible to accelerate the Li3PS4 formation reaction again even if the concentration of Li2S etc. present in the reaction field is low. At this time, since complexing agent 1, which has a superior ability to form a complex containing Li3PS4 and a halogen element compared to complexing agent 2, is present, the characteristics of both complexing agent 1 and complexing agent 2 are utilized, the Li3PS4 formation reaction proceeds, and the complex containing Li3PS4 and a halogen element formed is formed without stagnation.

[0045] Regarding the above-mentioned (3) property of complexing agent 2, that is, the ability to form a complex containing Li3PS4, it is known that, for example, dimethoxyethane (DME), which will be described later as an example of complexing agent 2, forms a complex containing Li3PS4 (see, for example, Chem. Mater. 2017, 29, 1830-1835, and Figure S4 in the Supporting Information thereof), and it is also known that, for example, tetrahydrofuran (THF) forms a complex containing Li3PS4 (see, for example, “Decomposition of Li3PS4·3THF forms β-Li3PS4” in J. Am. Chem. Soc. 2013, 135, 975-978, especially p. 976, and Figure S1 in the Supporting Information thereof). In this way, the above-mentioned condition (3) that the complexing agent 2 satisfies, that is, the property of being able to form a complex containing Li3PS4, is a property that can be specifically confirmed.

[0046] The complexing agent 2 can be used without any particular limitation as long as it has the above-mentioned properties, and is preferably a compound containing an element having a high affinity with lithium, such as a hetero element such as nitrogen, oxygen, or chlorine, and more preferably a compound having a group containing such a hetero element, because such a hetero element or group containing such a hetero element can be coordinated (bonded) with lithium. The hetero element present in the molecule of complexing agent 2 has a high affinity with lithium element, and is considered to have the ability to easily form a complex by bonding with Li3PS4 containing the PS4 structure, which is the main skeleton of the solid electrolyte produced by this embodiment. Therefore, it is considered that the formation of a complex containing Li3PS4 is accelerated by mixing the above raw material with complexing agent 2.

[0047] Among the hetero elements, oxygen is preferred, and the group containing oxygen is preferably one or more functional groups selected from ether and ester groups, and is particularly preferably an ether group. That is, ether compounds are particularly preferred as complexing agents. In addition, in relation to the complexing agent 1, it is preferred that the complexing agent 2 does not contain a nitrogen element as a hetero element. Therefore, in this embodiment, it is preferred that the complexing agent 1 contains a nitrogen element as a hetero element, and the complexing agent 2 does not contain a nitrogen element as a hetero element but contains an oxygen element. This makes it possible to effectively utilize the functions of the complexing agent 1 and the complexing agent 2 described above, and to improve the ionic conductivity of the resulting solid electrolyte.

[0048] Examples of such ether compounds include aliphatic ethers, alicyclic ethers, heterocyclic ethers, and aromatic ethers, and these compounds may be used alone or in combination.

[0049] More specifically, examples of aliphatic ethers include monoethers such as dimethyl ether, diethyl ether, diisopropyl ether, dibutyl ether, and tert-butyl methyl ether; diethers such as dimethoxymethane, dimethoxyethane, diethoxymethane, and diethoxyethane; polyethers having three or more ether groups, such as diethylene glycol dimethyl ether (diglyme) and triethylene oxide glycol dimethyl ether (triglyme); and ethers containing hydroxyl groups, such as diethylene glycol and triethylene glycol. The aliphatic ether preferably has 2 or more carbon atoms, more preferably 3 or more, and even more preferably 4 or more carbon atoms, and the upper limit is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less. The number of carbon atoms in the aliphatic hydrocarbon group in the aliphatic ether is preferably 1 or more, and the upper limit is preferably 6 or less, more preferably 4 or less, and even more preferably 3 or less.

[0050] Examples of alicyclic ethers include ethylene oxide, propylene oxide, tetrahydrofuran, tetrahydropyran, dimethoxytetrahydrofuran, cyclopentyl methyl ether, dioxane, and dioxolane. Examples of heterocyclic ethers include furan, benzofuran, benzopyran, dioxene, dioxin, morpholine, methoxyindole, and hydroxymethyldimethoxypyridine. The alicyclic ether and heterocyclic ether preferably have 3 or more, more preferably 4 or more, and the upper limit thereof is preferably 16 or less, more preferably 14 or less.

[0051] Examples of aromatic ethers include methyl phenyl ether (anisole), ethyl phenyl ether, dibenzyl ether, diphenyl ether, benzyl phenyl ether, and naphthyl ether. The aromatic ether preferably has 7 or more, more preferably 8 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and even more preferably 12 or less.

[0052] The ether compound used in the present embodiment may be substituted with a substituent such as an alkyl group, an alkenyl group, an alkoxyl group, a hydroxyl group, or a cyano group, or with a halogen atom.

[0053] The ether compound used in this embodiment is preferably an aliphatic ether, more preferably dimethoxyethane or tetrahydrofuran, from the viewpoint of obtaining higher ionic conductivity.

[0054] Examples of the ester compound include aliphatic esters, alicyclic esters, heterocyclic esters, and aromatic esters. These compounds may be used alone or in combination.

[0055] More specifically, examples of aliphatic esters include formic acid esters such as methyl formate, ethyl formate, triethyl formate, etc.; acetate esters such as methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, isobutyl acetate, etc.; propionate esters such as methyl propionate, ethyl propionate, propyl propionate, butyl propionate, etc.; oxalate esters such as dimethyl oxalate, diethyl oxalate, etc.; malonate esters such as dimethyl malonate, diethyl malonate, etc.; and succinate esters such as dimethyl succinate, diethyl succinate, etc. The number of carbon atoms in the aliphatic ester is preferably 2 or more, more preferably 3 or more, and even more preferably 4 or more, with the upper limit being preferably 10 or less, more preferably 8 or less, and even more preferably 7 or less. The number of carbon atoms in the aliphatic hydrocarbon group in the aliphatic ester is preferably 1 or more, more preferably 2 or more, and the upper limit being preferably 6 or less, more preferably 4 or less, and even more preferably 3 or less.

[0056] Examples of the alicyclic esters include methyl cyclohexanecarboxylate, ethyl cyclohexanecarboxylate, dimethyl cyclohexanedicarboxylate, dibutyl cyclohexanedicarboxylate, and dibutyl cyclohexenedicarboxylate. Examples of the heterocyclic esters include methyl pyridinecarboxylate, ethyl pyridinecarboxylate, propyl pyridinecarboxylate, methyl pyrimidinecarboxylate, ethyl pyrimidinecarboxylate, and lactones such as acetolactone, propiolactone, butyrolactone, and valerolactone. The alicyclic ester and heterocyclic ester each preferably have 3 or more, more preferably 4 or more, and the upper limit thereof is preferably 16 or less, more preferably 14 or less.

[0057] Examples of aromatic esters include benzoic acid esters such as methyl benzoate, ethyl benzoate, propyl benzoate, and butyl benzoate; phthalic acid esters such as dimethyl phthalate, diethyl phthalate, dibutyl phthalate, butyl benzyl phthalate, and dicyclohexyl phthalate; and trimellitic acid esters such as trimethyl trimellitate, triethyl trimellitate, tripropyl trimellitate, tributyl trimellitate, and trioctyl trimellitate. The aromatic ester preferably has 8 or more, more preferably 9 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and even more preferably 12 or less.

[0058] The ester compound used in the present embodiment may be substituted with a substituent such as an alkyl group, an alkenyl group, an alkoxyl group, a hydroxyl group, or a cyano group, or with a halogen element.

[0059] The ester compound used in the present embodiment is preferably an aliphatic ester, more preferably an acetate ester, and particularly preferably ethyl acetate, from the viewpoint of obtaining higher ionic conductivity.

[0060] In this embodiment, it is preferable to mix the complexing agent 2 after the complex formation reaction by the complexing agent 1 has progressed to a certain extent. There is no particular limitation on the method for determining the appropriate timing for adding complexing agent 2. For example, when lithium sulfide is used as one of the raw materials, a greater effect can be achieved by adding complexing agent 2 at the timing when the remaining amount of lithium sulfide present in the system has decreased to a certain value. Specifically, the complex formation reaction can be accelerated by adding the complexing agent 2 after the remaining amount of lithium sulfide has fallen to preferably 35 mol % or less, more preferably 30 mol % or less, and further preferably 25 mol % or less, based on the amount of lithium sulfide added. The amount of lithium sulfide remaining in the system can be measured by the method described in the Examples.

[0061] From the viewpoint of efficiently forming a complex, the molar ratio of the amount of complexing agent 2 added to the total molar amount of Li3PS4 that can be generated from two or more compounds satisfying the above (1) is preferably 1.0 or more and 5.0 or less, more preferably 2.0 or more and 4.0 or less, and even more preferably 2.5 or more and 3.5 or less.

[0062] [solvent] In this embodiment, when the raw material and the complexing agent are mixed, a solvent may be further added. When a solid complex is formed in a liquid complexing agent, if the complex is easily dissolved in the complexing agent, separation of the components may occur. Therefore, by using a solvent in which the complex is not dissolved, the dissolution of the components in the electrolyte precursor can be suppressed. In addition, by mixing the raw material and the complexing agent using a solvent, the complex formation is promoted, each main component can be more evenly present, and an electrolyte precursor in which the halogen element is more dispersed and fixed can be obtained, which makes it easier to achieve the effect of obtaining high ionic conductivity.

[0063] The method for producing a solid electrolyte according to the present embodiment is a so-called heterogeneous method, and it is preferable that the complex does not completely dissolve in the liquid complexing agent but precipitates. The solubility of the complex can be adjusted by adding a solvent. In particular, since halogen elements are easily eluted from the complex, the elution of the halogen elements can be suppressed by adding a solvent to obtain a desired complex. As a result, a crystalline solid electrolyte having high ionic conductivity can be obtained through an electrolyte precursor in which components such as halogens are dispersed.

[0064] Preferred examples of solvents having such properties include solvents having a solubility parameter of 10 or less. In this specification, the solubility parameter is a value δ ((cal / cm) calculated by the following formula (1) as described in various documents, such as "Chemical Handbook" (published in 2004, revised 5th edition, Maruzen Co., Ltd.). 3 ) 1 / 2 ) and is also called the Hildebrand parameter or SP value.

[0065]

number

[0066] By using a solvent with a solubility parameter of 10 or less, it is possible to make it difficult to dissolve the halogen element, the raw material containing the halogen element such as lithium halide, and further the component containing the halogen element constituting the cocrystal contained in the complex (for example, an aggregate in which lithium halide and the complexing agent are bonded), etc., compared to the above complexing agent, and it becomes easy to fix the halogen element in the complex, and the halogen element is present in a well-dispersed state in the obtained electrolyte precursor and further in the solid electrolyte, and it becomes easy to obtain a solid electrolyte having high ionic conductivity. That is, it is preferable that the solvent used in this embodiment has a property in which the complex does not dissolve. From the same viewpoint, the solubility parameter of the solvent is preferably 9.5 or less, more preferably 9.0 or less, and even more preferably 8.5 or less.

[0067] More specifically, the solvent used in the present embodiment can be a wide variety of solvents that have been conventionally used in the production of solid electrolytes. Examples of the solvent include hydrocarbon solvents such as aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, and aromatic hydrocarbon solvents; solvents containing carbon atoms such as alcohol-based solvents, ester-based solvents, aldehyde-based solvents, ketone-based solvents, ether-based solvents having 4 or more carbon atoms on one side, and solvents containing carbon atoms and heteroatoms; and the like. Among these, a solvent having a solubility parameter within the above-mentioned range may be appropriately selected and used.

[0068] More specifically, aliphatic hydrocarbon solvents such as hexane (7.3), pentane (7.0), 2-ethylhexane, heptane (7.4), octane (7.5), decane, undecane, dodecane, tridecane, etc.; alicyclic hydrocarbon solvents such as cyclohexane (8.2) and methylcyclohexane, etc.; benzene, toluene (8.8), xylene (8.8), mesitylene, ethylbenzene (8.8), tert-butylbenzene, trifluoromethylbenzene, nitrobenzene, chlorobenzene (9.5), chlorotoluene (8.8), bromobenzene, etc. Examples of aromatic hydrocarbon solvents include: alcohol solvents such as ethanol (12.7) and butanol (11.4); aldehyde solvents such as formaldehyde, acetaldehyde (10.3), and dimethylformamide (12.1); ketone solvents such as acetone (9.9) and methyl ethyl ketone; ether solvents such as dibutyl ether, cyclopentyl methyl ether (8.4), tert-butyl methyl ether, and anisole; and solvents containing carbon atoms and heteroatoms such as acetonitrile (11.9), dimethyl sulfoxide, and carbon disulfide. The numbers in parentheses in the above examples are SP values.

[0069] Among these solvents, aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, aromatic hydrocarbon solvents, and ether-based solvents are preferred, and from the viewpoint of obtaining a more stable and high ion conductivity, heptane, cyclohexane, toluene, ethylbenzene, diethyl ether, diisopropyl ether, dibutyl ether, dimethoxyethane, cyclopentyl methyl ether, tert-butyl methyl ether, and anisole are more preferred, diethyl ether, diisopropyl ether, and dibutyl ether are even more preferred, and diisopropyl ether and dibutyl ether are even more preferred, and cyclohexane is particularly preferred. The solvent used in this embodiment is preferably the organic solvent exemplified above, and is an organic solvent different from the complexing agent. In this embodiment, these solvents may be used alone or in combination.

[0070] [mixture] In this embodiment, the method includes a first step of mixing the raw material and the complexing agent 1, and a second step of further mixing the complexing agent 2 after the first step. In this embodiment, the raw material and the complexing agent may be mixed in either a solid or liquid form, but since the raw material usually contains a solid and the complexing agent is liquid, they are usually mixed in a form in which the solid raw material exists in the liquid complexing agent. In addition, when mixing the raw material and the complexing agent, a solvent may be further mixed as necessary. Hereinafter, in the section explaining the mixing of the raw material and the complexing agent, unless otherwise specified, the complexing agent also includes a solvent added as necessary.

[0071] There is no particular limitation on the method of mixing the raw materials and the complexing agent, and the raw materials and the complexing agent may be mixed in a device capable of mixing the raw materials and the complexing agent. For example, it is preferable to supply the complexing agent into a tank, operate the stirring blade, and then gradually add the raw materials, since this provides a good mixing state of the raw materials and improves the dispersibility of the raw materials. However, when a halogen element is used as a raw material, the raw material may not be solid, specifically, fluorine and chlorine are gaseous, and bromine is liquid, at room temperature and pressure. In such a case, for example, if the raw material is liquid, it may be supplied to the tank together with a complexing agent separately from other solid raw materials, and if the raw material is gaseous, it may be supplied by blowing into the mixture of the solid raw material and the complexing agent.

[0072] The method for producing a solid electrolyte according to the present embodiment is characterized by including mixing the raw material and the complexing agent, and can be produced by a method that does not use equipment generally called a pulverizer, such as a media-type pulverizer such as a ball mill or a bead mill, which is used for the purpose of pulverizing a solid raw material. In the method for producing a solid electrolyte according to the present embodiment, the raw material and the complexing agent contained in the inclusion are mixed and a complex can be formed by simply mixing the raw material and the complexing agent. In order to shorten the mixing time for obtaining the complex or to pulverize the mixture, the mixture of the raw material and the complexing agent may be pulverized by a pulverizer, but from the viewpoint of improving productivity, it is preferable not to use a pulverizer in the first step, that is, it is preferable not to perform pulverization and mixing in the first step.

[0073] An example of an apparatus for mixing the raw material and the complexing agent is a mechanical stirring mixer equipped with stirring blades in a tank. Examples of mechanical stirring mixers include high-speed stirring mixers and double-arm mixers, and high-speed stirring mixers are preferably used from the viewpoint of increasing the uniformity of the raw material in the mixture of the raw material and the complexing agent and obtaining higher ionic conductivity. Examples of high-speed stirring mixers include vertical shaft rotary mixers and horizontal shaft rotary mixers, and either type of mixer may be used.

[0074] The shape of the impeller used in the mechanical stirring mixer includes anchor type, blade type, arm type, ribbon type, multi-stage blade type, double arm type, shovel type, double-shaft blade type, flat blade type, C-shaped blade type, etc., and from the viewpoint of improving the uniformity of the raw material in the raw material and obtaining higher ion conductivity, the shovel type, flat blade type, C-shaped blade type, etc. are preferred. In addition, in the mechanical stirring mixer, it is preferable to install a circulation line that discharges the material to be stirred outside the mixer and then returns it to the inside of the mixer. This allows the raw material with a high specific gravity, such as lithium halide, to be stirred without settling or stagnation, making it possible to mix more uniformly.

[0075] The location of the circulation line is not particularly limited, but it is preferable to install it at a location where it is discharged from the bottom of the mixer and returned to the top of the mixer. This makes it easier to mix the raw materials that tend to settle by convection caused by circulation. Furthermore, it is preferable that the return port is located below the liquid surface of the object to be mixed. This makes it possible to prevent the object to be mixed from splashing and adhering to the wall surface inside the mixer.

[0076] The temperature conditions when mixing the raw materials and the complexing agent are not particularly limited, and are, for example, −30 to 100° C., preferably −10 to 50° C., and more preferably about room temperature (23° C.) (for example, about room temperature ±5° C.) The mixing time is about 0.1 to 150 hours, and from the viewpoint of more uniform mixing and obtaining higher ionic conductivity, is preferably 1 to 120 hours, more preferably 4 to 100 hours, and even more preferably 8 to 80 hours.

[0077] By mixing the raw material with the complexing agent, a complex is obtained in which the lithium, sulfur, phosphorus and halogen elements contained in the raw material are directly bonded to each other with and / or without the complexing agent due to the action of the complexing agent. That is, in the method for producing a solid electrolyte of this embodiment, the complex obtained by mixing the raw material with the complexing agent is composed of the complexing agent, lithium, sulfur, phosphorus and halogen. The complex obtained in this embodiment is not completely dissolved in the complexing agent, which is a liquid, and is usually solid, so in this embodiment, a suspension in which the complex is suspended in the complex and a solvent added as necessary is obtained. Therefore, the method for producing a solid electrolyte of this embodiment corresponds to a heterogeneous system in a so-called liquid phase method.

[0078] (Li2S remaining) In this embodiment, the amount of Li2S remaining at the time when the first step is completed is preferably 1.0% or more, more preferably 3.0% or more, and even more preferably 5.0% or more, and the upper limit is preferably 35.0% or less, more preferably 30.0% or less, and even more preferably 25.0% or less. By setting the amount of Li2S remaining within the above range, a solid electrolyte having high ionic conductivity can be obtained more efficiently. In this specification, the "Li2S remaining amount" refers to the amount of unreacted Li2S in the reaction field when Li2S is used as a raw material, determined by the method described in the Examples, and is a numerical value that serves as an index for understanding the progress of the reaction.

[0079] Furthermore, the lower the remaining amount of Li2S at the time when the second step is completed, the better. Specifically, it is preferably 20.0% or less, more preferably 15.0% or less, even more preferably 10.0% or less, still more preferably 5.0% or less, and particularly preferably 2.5% or less. According to the manufacturing method of this embodiment, by using two different complexing agents 1 and 2 in sequence, the amount of remaining LiS can be suppressed to an extremely small amount as described above, so that a solid electrolyte having high ionic conductivity can be efficiently obtained.

[0080] [Drying] The method for producing a solid electrolyte according to the present embodiment may include a step of drying the suspension obtained after the second step. This allows a powder of an electrolyte precursor to be obtained. By drying in advance, it becomes possible to efficiently perform heating. The drying and the subsequent heating may be performed in the same step.

[0081] Drying can be performed at a temperature according to the type of complexing agent and solvent remaining in the complex. For example, drying can be performed at a temperature equal to or higher than the boiling point of the complexing agent or solvent. Drying can be performed by volatilizing the complexing agent and solvent by drying under reduced pressure (vacuum drying) using a vacuum pump or the like at usually 5 to 100°C, preferably 10 to 85°C, more preferably 15 to 70°C, and even more preferably at about room temperature (23°C) (for example, about room temperature ±5°C). Unlike the complexing agent, the solvent is not easily incorporated into the complex, and therefore the amount of the solvent that can be contained in the complex is usually 3 mass % or less, preferably 2 mass % or less, and more preferably 1 mass % or less.

[0082] The drying may be performed by filtration using a glass filter or the like, solid-liquid separation by decantation, or solid-liquid separation using a centrifuge, etc. In this embodiment, after the solid-liquid separation, drying may be performed under the above-mentioned temperature conditions. Specifically, solid-liquid separation can be easily performed by decantation, in which the suspension is transferred to a container, and after the solid has settled, the complexing agent and the solvent added as necessary are removed as the supernatant, or by filtration using a glass filter having a pore size of about 10 to 200 μm, preferably 20 to 150 μm.

[0083] The complex is characterized in that a peak different from the peak derived from the raw materials is observed in the X-ray diffraction pattern in X-ray diffraction measurement, and preferably includes a co-crystal composed of a complexing agent, lithium, sulfur, phosphorus, and a halogen. When the raw materials are simply mixed, only a peak derived from the raw materials is observed, and when the raw materials are mixed with a complexing agent, a peak different from the peak derived from the raw materials is observed, so the complex (co-crystal) has a structure that is clearly different from the raw materials themselves contained in the raw materials. This has been specifically confirmed in the Examples. Examples of measurement of the X-ray diffraction patterns of the complex (co-crystal) and each raw material such as lithium sulfide are shown in Figures 1 and 2, respectively. From the X-ray diffraction pattern, it can be seen that the complex (co-crystal) has a predetermined crystal structure. In addition, the diffraction pattern does not include the diffraction pattern of any of the raw materials such as lithium sulfide shown in Figure 2, and it can be seen that the complex (co-crystal) has a crystal structure different from the raw materials.

[0084] In addition, the complex (co-crystal) is characterized by having a structure different from that of the crystalline solid electrolyte. This has also been specifically confirmed in the Examples. FIG. 1 also shows the X-ray diffraction pattern of the crystalline solid electrolyte of Example 1, and it can be seen that it is different from the diffraction pattern of the complex (co-crystal). In addition, the complex (co-crystal) has a specific crystal structure, and is also different from the amorphous solid electrolyte having a broad pattern shown in FIG. 1.

[0085] The cocrystal is composed of a complexing agent, lithium element, sulfur element, phosphorus element, and a halogen element, and is typically considered to form a complex structure in which lithium element and other elements are directly bonded with and / or without the intervention of a complexing agent. Here, the fact that the complexing agent forms a cocrystal can be confirmed by, for example, gas chromatography analysis. Specifically, the complexing agent contained in the cocrystal can be quantified by dissolving a powder of the complex in methanol and performing gas chromatography analysis of the resulting methanol solution. The content of the complexing agent in the complex varies depending on the molecular weight of the complexing agent, but is usually about 10% by mass to 70% by mass, preferably 15% by mass to 65% by mass.

[0086] In the method for producing a solid electrolyte according to the present embodiment, it is preferable to form a co-crystal containing a halogen element in terms of improving ionic conductivity. By using the complexing agent 1, raw materials containing lithium and halogen, such as Li3PS4 and lithium halide, are bonded (coordinated) via the complexing agent 1, and it becomes easier to obtain a co-crystal in which the halogen element is more dispersed and fixed, thereby improving ionic conductivity.

[0087] The fact that the halogen element in the complex forms a co-crystal can be confirmed by checking that a predetermined amount of the halogen element is still contained in the complex even after solid-liquid separation of the suspension. This is because halogen elements that do not form a co-crystal are more easily dissolved than halogen elements that form a co-crystal and are discharged into the liquid of solid-liquid separation. It can also be confirmed by checking that the ratio of the halogen element in the complex or solid electrolyte is not significantly reduced compared to the ratio of the halogen element supplied from the raw material by composition analysis of the complex or solid electrolyte using ICP analysis (inductively coupled plasma atomic emission spectroscopy). The amount of the halogen element remaining in the complex is preferably 30% by mass or more, more preferably 35% by mass or more, and even more preferably 40% by mass or more, based on the charged composition. The upper limit of the amount of the halogen element remaining in the complex is 100% by mass.

[0088] [heating] The method for producing a solid electrolyte of the present embodiment preferably includes heating an electrolyte precursor to obtain an amorphous solid electrolyte, and heating the electrolyte precursor or the amorphous solid electrolyte to obtain a crystalline solid electrolyte. By including the step of heating the electrolyte precursor, the complexing agent in the electrolyte precursor is removed, and an amorphous solid electrolyte or a crystalline solid electrolyte containing lithium, sulfur, phosphorus, and a halogen element is obtained. Here, the removal of the complexing agent in the electrolyte precursor is supported by the fact that the complexing agent constitutes a cocrystal of the electrolyte precursor from the results of X-ray diffraction patterns, gas chromatography analysis, and the like, and that the solid electrolyte obtained by removing the complexing agent by heating the electrolyte precursor has the same X-ray diffraction pattern as the solid electrolyte obtained by the conventional method without using the complexing agent.

[0089] In the manufacturing method of the present embodiment, the solid electrolyte is obtained by removing the complexing agent in the electrolyte precursor by heating the electrolyte precursor, and the less the complexing agent in the solid electrolyte, the better, but the complexing agent may be contained to an extent that does not impair the performance of the solid electrolyte. The content of the complexing agent in the solid electrolyte is usually 10 mass % or less, preferably 5 mass % or less, more preferably 3 mass % or less, and further preferably 1 mass % or less.

[0090] In the manufacturing method of the present embodiment, the crystalline solid electrolyte may be obtained by heating an electrolyte precursor, or the electrolyte precursor may be heated to obtain an amorphous solid electrolyte, and the amorphous solid electrolyte may then be heated. That is, the manufacturing method of the present embodiment can also produce an amorphous solid electrolyte. Conventionally, in order to obtain a crystalline solid electrolyte having high ionic conductivity, for example, a solid electrolyte having a thiolicon region II type crystal structure described later, it was necessary to prepare an amorphous solid electrolyte by mechanical pulverization such as mechanical milling, or other melt quenching treatments, and then heat the amorphous solid electrolyte to obtain it. However, the manufacturing method of the present embodiment is superior to the conventional manufacturing method using mechanical milling, etc., in that a crystalline solid electrolyte having a thiolicon region II type crystal structure can be obtained by a method that does not involve mechanical pulverization or other melt quenching treatments.

[0091] In the method for producing a solid electrolyte according to the present embodiment, whether to obtain an amorphous solid electrolyte, a crystalline solid electrolyte, or further to obtain a crystalline solid electrolyte after obtaining an amorphous solid electrolyte, or to obtain a crystalline solid electrolyte directly from an electrolyte precursor is appropriately selected as desired, and can be adjusted by the heating temperature, heating time, etc.

[0092] The heating temperature of the electrolyte precursor may be determined according to the structure of the crystalline solid electrolyte obtained by heating the amorphous solid electrolyte (or electrolyte precursor), for example, when obtaining an amorphous solid electrolyte. Specifically, the amorphous solid electrolyte (or electrolyte precursor) is subjected to differential thermal analysis (DTA) at a temperature rise rate of 10°C / min using a differential thermal analyzer (DTA device), and the heating temperature is preferably set to 5°C or less, more preferably 10°C or less, and even more preferably 20°C or less, starting from the temperature of the top of the exothermic peak observed on the lowest temperature side. There is no particular limit to the lower limit, but it may be set to about -40°C or more, which is the temperature of the top of the exothermic peak observed on the lowest temperature side. By setting the temperature range, an amorphous solid electrolyte can be obtained more efficiently and reliably. The heating temperature for obtaining an amorphous solid electrolyte cannot be generally defined because it varies depending on the structure of the crystalline solid electrolyte to be obtained. Generally, however, the heating temperature is preferably 135° C. or lower, more preferably 130° C. or lower, and even more preferably 125° C. or lower. There is no particular lower limit, but the heating temperature is preferably 90° C. or higher, more preferably 100° C. or higher, and even more preferably 110° C. or higher.

[0093] In addition, when the crystalline solid electrolyte is obtained by heating the amorphous solid electrolyte or directly from the electrolyte precursor, the heating temperature may be determined according to the structure of the crystalline solid electrolyte, and is preferably higher than the heating temperature for obtaining the amorphous solid electrolyte. Specifically, the amorphous solid electrolyte (or electrolyte precursor) is subjected to differential thermal analysis (DTA) at a temperature rise rate of 10°C / min using a differential thermal analyzer (DTA device), and the temperature is preferably set to 5°C or higher, more preferably 10°C or higher, and even more preferably 20°C or higher, starting from the peak top temperature of the exothermic peak observed on the lowest temperature side. There is no particular limit to the upper limit, but it may be about 40°C or lower. By setting the temperature range, the crystalline solid electrolyte can be obtained more efficiently and reliably. The heating temperature for obtaining a crystalline solid electrolyte cannot be generally defined because it varies depending on the structure of the crystalline solid electrolyte to be obtained. Generally, however, the heating temperature is preferably 130° C. or higher, more preferably 135° C. or higher, and even more preferably 140° C. or higher. There is no particular upper limit, but the heating temperature is preferably 300° C. or lower, more preferably 280° C. or lower, and even more preferably 250° C. or lower.

[0094] The heating time is not particularly limited as long as the desired amorphous solid electrolyte or crystalline solid electrolyte can be obtained, but is preferably, for example, 1 minute or more, more preferably 10 minutes or more, even more preferably 30 minutes or more, and even more preferably 1 hour or more. The upper limit of the heating time is not particularly limited, but is preferably 24 hours or less, more preferably 10 hours or less, even more preferably 5 hours or less, and even more preferably 3 hours or less.

[0095] Moreover, the heating is preferably carried out in an inert gas atmosphere (e.g., nitrogen atmosphere, argon atmosphere) or reduced pressure atmosphere (particularly in vacuum). This is because deterioration (e.g., oxidation) of the crystalline solid electrolyte can be prevented. The heating method is not particularly limited, and examples thereof include a method using a hot plate, a vacuum heating device, an argon gas atmosphere furnace, and a baking furnace. Furthermore, industrially, a horizontal dryer having a heating means and a feeding mechanism, a horizontal vibration fluidized dryer, etc. can also be used, and may be selected according to the amount of processing to be heated.

[0096] [Amorphous solid electrolyte] The amorphous solid electrolyte obtained by the method for producing a solid electrolyte of this embodiment contains lithium, sulfur, phosphorus and halogen elements. Representative examples include solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr, and solid electrolytes further containing other elements such as oxygen and silicon, such as Li2S-P2S5-Li2O-LiI and Li2S-SiS2-P2S5-LiI. From the viewpoint of obtaining higher ionic conductivity, solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr, are preferred. The types of elements constituting the amorphous solid electrolyte can be confirmed, for example, by an ICP emission spectroscopic analyzer.

[0097] When the amorphous solid electrolyte obtained by the method for producing a solid electrolyte of this embodiment contains at least Li2S-P2S5, the molar ratio of Li2S to P2S5 is preferably 65-85:15-35, more preferably 70-80:20-30, and even more preferably 72-78:22-28, from the viewpoint of obtaining higher ionic conductivity. In the case where the amorphous solid electrolyte obtained by the method for producing a solid electrolyte of this embodiment is, for example, Li2S-P2S5-LiI-LiBr, the total content of lithium sulfide and diphosphorus pentasulfide is preferably 60 to 95 mol%, more preferably 65 to 90 mol%, and even more preferably 70 to 85 mol%. The ratio of lithium bromide to the total of lithium bromide and lithium iodide is preferably 1 to 99 mol%, more preferably 20 to 90 mol%, even more preferably 40 to 80 mol%, and particularly preferably 50 to 70 mol%.

[0098] In the amorphous solid electrolyte obtained by the method for producing a solid electrolyte of the present embodiment, the compounding ratio (molar ratio) of lithium element, sulfur element, phosphorus element, and halogen element is preferably 1.0-1.8:1.0-2.0:0.1-0.8:0.01-0.6, more preferably 1.1-1.7:1.2-1.8:0.2-0.6:0.05-0.5, and further preferably 1.2-1.6:1.3-1.7:0.25-0.5:0.08-0.4. In addition, when bromine and iodine are used in combination as the halogen elements, the compounding ratio (molar ratio) of lithium element, sulfur element, phosphorus element, bromine, and iodine is preferably 1.0-1.8:1.0-2.0:0.1-0.8:0.01-0.3:0.01-0.3, more preferably 1.1-1.7:1.2-1.8:0.2-0.6:0.02-0.25:0.02-0.25, more preferably 1.2-1.6:1.3-1.7:0.25-0.5:0.03-0.2:0.03-0.2, and still more preferably 1.35-1.45:1.4-1.7:0.3-0.45:0.04-0.18:0.04-0.18. By setting the compounding ratio (molar ratio) of lithium element, sulfur element, phosphorus element and halogen element within the above range, it becomes easier to obtain a solid electrolyte having a thiolithicon region II type crystal structure described later and having higher ionic conductivity.

[0099] The shape of the amorphous solid electrolyte is not particularly limited, but may be, for example, particulate. The average particle diameter (D 50 ) can be, for example, in the range of 0.01 μm to 500 μm, or further, 0.1 to 200 μm.

[0100] [Crystalline solid electrolyte] The crystalline solid electrolyte obtained by the method for producing a solid electrolyte according to the present embodiment may be a so-called glass ceramic obtained by heating an amorphous solid electrolyte to a crystallization temperature or higher. Examples of the crystal structure include a Li3PS4 crystal structure, a Li4P2S6 crystal structure, a Li7PS6 crystal structure, a Li7P3S 11 Examples of such structures include a crystal structure having peaks at 2θ=approximately 20.2° and 23.6° (for example, JP 2013-16423 A).

[0101] Li 4-x Ge 1-x P x S4 thio-LISICON Region II crystal structure (Kanno et al., Journal of The Electrochemical Society, 148(7)A742-746(2001)), Li 4-x Ge 1-x P x Examples of the crystal structure include a crystal structure similar to the S4-based thio-LISICON Region II type (see Solid State Ionics, 177 (2006), 2721-2725). The crystal structure of the crystalline solid electrolyte obtained by the method for producing a solid electrolyte of this embodiment is preferably the thio-LISICON Region II type crystal structure among the above, since it has a higher ionic conductivity. Here, the "thio-LISICON Region II type crystal structure" refers to a Li 4-x Ge 1-x P x S4 thio-LISICON Region II crystal structure, Li 4-x Ge 1-x P x This indicates that the crystal structure is similar to that of the S4 thio-LISICON Region II type. In addition, the crystalline solid electrolyte obtained by the manufacturing method of this embodiment may contain the above-mentioned thiolicon region II type crystal structure or may contain it as a main crystal, but from the viewpoint of obtaining higher ionic conductivity, it is preferable that it contains it as a main crystal. In this specification, "containing it as a main crystal" means that the ratio of the target crystal structure among the crystal structures is 80% or more, preferably 90% or more, and more preferably 95% or more. In addition, the crystalline solid electrolyte obtained by the manufacturing method of this embodiment is preferably one that does not contain crystalline Li3PS4 (β-Li3PS4) from the viewpoint of obtaining higher ionic conductivity.

[0102] In X-ray diffraction measurements using CuKα radiation, the diffraction peaks of the Li3PS4 crystal structure appear, for example, at 2θ = 17.5°, 18.3°, 26.1°, 27.3°, and 30.0°, the diffraction peaks of the Li4P2S6 crystal structure appear, for example, at 2θ = 16.9°, 27.1°, and 32.5°, the diffraction peaks of the Li7PS6 crystal structure appear, for example, at 2θ = 15.3°, 25.2°, 29.6°, and 31.0°, and the diffraction peaks of the Li7P3S 11 Diffraction peaks of the crystal structure appear, for example, at 2θ = 17.8°, 18.5°, 19.7°, 21.8°, 23.7°, 25.9°, 29.6°, and 30.0°. 4-x Ge 1-x P x The diffraction peaks of the S4 thio-LISICON Region II crystal structure appear, for example, at 2θ = 20.1°, 23.9°, and 29.5°, and Li 4-x Ge 1-x P x Diffraction peaks of a crystal structure similar to the S4 thio-LISICON Region II type appear, for example, at 2θ=20.2 and 23.6°. Note that these peak positions may vary within a range of ±0.5°.

[0103] As described above, in the present embodiment, when the thiolicon region II type crystal structure is obtained, it is preferable that it does not contain crystalline Li3PS4 (β-Li3PS4). Figure 1 shows an example of X-ray diffraction measurement of the crystalline solid electrolyte obtained by the manufacturing method of the present embodiment. Figure 2 shows an example of X-ray diffraction measurement of crystalline Li3PS4 (β-Li3PS4). As can be understood from FIGS. 1 and 2 and the like, the solid electrolyte of the present embodiment either does not have diffraction peaks at 2θ = 17.5° and 26.1° found in crystalline Li3PS4, or even if it has such peaks, the detected peaks are extremely small compared to the diffraction peaks of the thio-LiSi region II-type crystal structure. In the present embodiment, it is preferable that the obtained solid electrolyte does not contain crystalline Li3PS4 (β-Li3PS4) as described above, that is, it is preferable that it does not have diffraction peaks at 2θ = 17.5° and 26.1° found in crystalline Li3PS4.

[0104] Having the above-mentioned structural skeleton of Li7PS6 and having a composition formula Li in which part of P is substituted with Si 7-x P 1-y Si y S6 and Li 7+x P 1-y Si y The crystal structure represented by S6 (where x is -0.6 to 0.6 and y is 0.1 to 0.6) is cubic or orthorhombic, preferably cubic, and in X-ray diffraction measurement using CuKα rays, mainly at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°. The above composition formula Li 7-x-2y PS 6-x-y Cl x (where 0.8 ≤ x ≤ 1.7 and 0 < y ≤ -0.25x + 0.5) is preferably cubic, and in X-ray diffraction measurement using CuKα rays, mainly at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°. Also, the above composition formula Li 7-x PS 6-x Ha x (where Ha is Cl or Br and x is preferably 0.2 to 1.8) is preferably cubic, and in X-ray diffraction measurement using CuKα rays, mainly at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°. Note that these peak positions may shift within a range of ±0.5°.

[0105] The shape of the crystalline solid electrolyte is not particularly limited, but may be, for example, particulate. The average particle diameter (D 50 ) can be, for example, in the range of 0.01 μm to 500 μm, or further, 0.1 to 200 μm. EXAMPLES

[0106] The present invention will now be described in detail with reference to examples, but the present invention is not limited to these examples in any way.

[0107] (Powder XRD diffraction and measurement of remaining Li2S) Powder X-ray diffraction (XRD) measurement and calculation of the remaining amount of Li2S in the solid electrolyte were carried out as follows. The amorphous solid electrolyte powder obtained in the examples and comparative examples was filled into a groove with a diameter of 20 mm and a depth of 0.2 mm, and was smoothed with glass to prepare a sample. This sample was sealed with a Kapton film for XRD and measured under the following conditions without being exposed to air. When measuring the amount of Li2S remaining after adding complexing agent 1 and stirring, 10 ml of the slurry after adding complexing agent 1 and stirring (before adding complexing agent 2 in the case of adding complexing agent 2) was extracted and dried under reduced pressure at room temperature to obtain a powder electrolyte precursor, which was then subjected to reduced pressure at 110°C for 2 hours to obtain an amorphous solid electrolyte. In addition, powder X-ray diffraction (XRD) of the raw materials used in the examples was also performed in the same manner as for the amorphous solid electrolyte. Measurement equipment: D2 PHASER, manufactured by Bruker Corporation Tube voltage: 30kV Tube current: 10mA X-ray wavelength: Cu-Kα ray (1.5418Å) Optical system: Concentration method Slit configuration: Solar slit 4°, divergence slit 1mm, Kβ filter (Ni plate) Detector: Semiconductor detector Measurement range: 2θ=10-60deg Step width, scan speed: 0.05deg, 0.05deg / sec

[0108] The measurement results were analyzed using Excel Solver to confirm the amount of remaining raw materials. The 2θ of the raw data was A, the peak intensity was B, and the baseline and glass intensity used in the calculation were C and D, respectively. When calculating the peak intensity for the baseline, the following empirical calculations were made for each 2θ from the measurement system. C=-45.72*A+4600-457.2 The glass strength D was calculated by the following formula, where the peak angles are E, F, G, and H, the widths are I, J, K, and L, and the strengths are M, N, O, and P.

[0109]

number

[0110] Furthermore, the background correction data for calculation is Q as follows: Q=BC The peak position of the raw material Li2S at the beginning of the reaction and the calculated peak shift of the Li2S peak are designated as R, and R is added to all peaks and reflected in the above Q. In addition, the peak intensity at the beginning of the reaction of Li2S is designated as S, and the peak intensity is fitted by multiplying the peak intensity S at the beginning of the reaction by a coefficient T. The sum of the fitting residuals is designated as U, which is given as follows.

[0111]

number

[0112] In calculations using the solver function, E, F, G, H, I, J, K, L, M, N, O, P, R, and T were used as variables, and calculations were performed so that U was minimized using the GRG nonlinearity, and the remaining amount of Li2S was fitted.

[0113] (Measurement of ionic conductivity) In this example, the ionic conductivity was measured as follows. From the crystalline solid electrolytes obtained in the examples and comparative examples, a 10 mm diameter (cross-sectional area S: 0.785 cm 2) and a height (L) of 0.1-0.3 cm were molded into a circular pellet to prepare a sample. Electrode terminals were attached to the top and bottom of the sample, and measurements were made at 25°C using an AC impedance method (frequency range: 5 MHz-0.5 Hz, amplitude: 10 mV) to obtain a Cole-Cole plot. The real part Z' (Ω) at the point where -Z'' (Ω) is minimum near the right end of the arc observed in the high frequency region was taken as the bulk resistance R (Ω) of the electrolyte, and the ionic conductivity σ (S / cm) was calculated according to the following formula: R=ρ(L / S) σ=1 / ρ

[0114] (Production Example 1) In a Schlenk flask (capacity: 500 mL) with a stirrer, 15.87 g of lithium sulfide (Li2S) was introduced as a compound satisfying (1) under a nitrogen atmosphere. After rotating the stirrer, 300 mL of cyclohexane was added, followed by 6.26 g of iodine (I2) as a compound satisfying (1), and stirring at room temperature for 2 hours. After that, 3.94 g of bromine (Br2) was added as a compound satisfying (1), and stirring was continued at room temperature for 12 hours, followed by stirring at 50°C for another 3 hours. The slurry was left to stand to allow the solids to settle, and 190 mL of the supernatant was removed, followed by adding 190 mL of cyclohexane. This decantation was repeated three times to obtain a cyclohexane slurry containing lithium sulfide, lithium iodide, and lithium bromide.

[0115] (Production Example 2: Production of Li3PS4-TMEDA Complex) Under an inert gas atmosphere in a glove box, 10 g of lithium sulfide (Li2S) and diphosphorus pentasulfide (P2S5) were weighed in a Schlenk flask containing a stirrer so that the molar ratio was 3:1, and cooled with a mixture of acetone and liquid nitrogen. After cooling for 30 minutes, 100 mL of tetrahydrofuran (THF) was added under inert gas while stirring with a stirrer, and the mixture was stirred for another 3 days. The resulting slurry was filtered, and the resulting solid was washed five times with THF, and the solvent was dried in vacuum to obtain a Li3PS4-3THF complex. This complex was dried in vacuum at 90°C for 5 hours to obtain amorphous g-Li3PS4. 5 g of the g-Li3PS4 was weighed out in a Schlenk flask containing a stirrer in an inert gas atmosphere in a glove box, and 20 mL of N,N,N,N-tetramethylethane-1,2-diamine (N,N,N,N-tetramethylethylenediamine, TMEDA) was added and stirred under inert gas flow. After reacting for 3 days, the solvent was vacuum dried (room temperature) to obtain a Li3PS4-TMEDA complex.

[0116] (Production Example 3: Production of LiI-TMEDA Complex) A LiI-TMEDA complex was prepared in the same manner as in Production Example 2 above, except that 5 g of LiI was weighed out instead of g-Li3PS4, the solvent was vacuum dried (at room temperature), and then the drying treatment was performed at 100°C.

[0117] (FT-IR analysis (diffuse reflectance method)) The complexes obtained in Production Examples 2 and 3 and TMEDA were analyzed by the following methods. The analysis results are shown in FIG. Measurement equipment: FT-IR spectrometer "FT / IR-6200" manufactured by JASCO Corporation Measurement method: Diffuse reflectance method Measurement wave number range: 400~4000cm-1 Light source: High-brightness ceramic light source (halogen lamp) Detector: DLATGS Resolution: 4cm-1 Measurement time: 1.2 seconds / time Number of times: 100 Measurement conditions: Measurement using a KBr diffuse reflectance cell

[0118] Example 1 21.93 g of diphosphorus pentasulfide (P2S5) and 100 mL of cyclohexane were added to the slurry containing lithium sulfide, lithium iodide, and lithium bromide, which are compounds satisfying (1), obtained by Production Example 1, and transferred to a 500 mL separable flask equipped with a circulation line and a rotor blade. 103 mL of tetramethylethylenediamine (complexing agent 1) was added thereto, and mixing by circulation stirring (first step) was started at room temperature with the rotor blade rotation speed of 200 rpm and the pump flow rate of 550 mL / min. After 48 hours had passed, the remaining amount of Li2S after mixing in the first step was 22%. Next, 48 mL of tetrahydrofuran (complexing agent 2, hereinafter also referred to as "THF") was added (an amount of 3 in molar ratio with respect to the estimated amount of Li3PS4 obtained from the above raw materials), and mixing (second step) was performed by continuing circulation stirring for another 24 hours, and the obtained slurry was dried under reduced pressure at room temperature to obtain a powdered electrolyte precursor. Next, the pressure was reduced at 110°C for 2 hours to obtain an amorphous solid electrolyte. The obtained amorphous solid electrolyte was subjected to XRD measurement, and it was confirmed that there were no peaks other than those derived from the electrolyte precursor and raw materials in the X-ray diffraction spectrum. The X-ray diffraction spectrum is shown in Figure 1. In addition, the amount of Li2S remaining after the mixing in the second step was calculated to be 1%. Furthermore, the amorphous solid electrolyte was subjected to reduced pressure at 200°C for 2 hours to obtain a crystalline solid electrolyte. The obtained crystalline solid electrolyte was subjected to XRD measurement. The results are shown in Figure 1. In the X-ray diffraction spectrum of the crystalline solid electrolyte, crystallization peaks were detected mainly at 2θ = 20.2° and 23.6°, and it had a thiolicon region II type crystal structure and did not have diffraction peaks at 2θ = 17.5° and 26.1°. The ionic conductivity was measured to be 3.96 × 10 -3 (S / cm), confirming that the material had high ionic conductivity. The results are shown in Table 1.

[0119] (Examples 2 to 5) In Example 1, the electrolyte precursor, the amorphous solid electrolyte, and the crystalline solid electrolyte were obtained in the same manner as in Example 1, except that the amount of solvent added, the mixing time in the first step, the type and amount of complexing agent 2, and the mixing time in the second step were as shown in Table 1. In addition, the Li2S remaining amount after adding and mixing the complexing agent 1 (after mixing in the first step) and the Li2S remaining amount in the finally obtained amorphous solid electrolyte (after mixing in the second step) were calculated in the same manner as in Example 1. In addition, the XRD measurement and the ionic conductivity measurement were performed on the obtained crystalline solid electrolyte in the same manner as in Example 1. The results of Examples 2 to 5 are shown in Table 1, and the results of the XRD measurement of Examples 2, 4, and 5 are shown in Figures 3 to 5, respectively.

[0120] In the X-ray diffraction spectrum of the electrolyte precursor obtained in this embodiment, peaks different from those derived from the raw materials used were observed, and the X-ray diffraction pattern was different from that of the amorphous solid electrolyte and the crystalline solid electrolyte. In addition, powder X-ray diffraction (XRD) measurements were also performed on the raw materials used in this embodiment 1 (lithium bromide and lithium iodide) and the raw materials used in other embodiments (lithium sulfide, diphosphorus pentasulfide), as well as amorphous Li3PS4 and crystalline Li3PS4 prepared as references for the X-ray diffraction patterns, and the X-ray diffraction spectra are shown in FIG. 2. The X-ray diffraction spectrum of the electrolyte precursor showed an X-ray diffraction pattern different from that of the raw materials. It was confirmed that the X-ray diffraction spectrum of the amorphous solid electrolyte had no peaks other than those derived from the raw materials.

[0121] Comparative Example 1 An electrolyte precursor and an amorphous solid electrolyte were obtained in the same manner as in Example 1, except that cyclohexane was 150 mL, complexing agent 2 was not added, and circulation stirring was continued for 30 hours. The amount of Li2S remaining in the obtained amorphous solid electrolyte was calculated in the same manner as in Example 1, and it was found to be 37%, indicating that the synthesis reaction had not progressed sufficiently. The results are shown in Table 1.

[0122] Comparative Example 2 An electrolyte precursor and an amorphous solid electrolyte were obtained in the same manner as in Comparative Example 1, except that the circulation stirring time was changed to 48 hours. The amount of Li2S remaining in the obtained amorphous solid electrolyte was calculated in the same manner as in Example 1. The results are shown in Table 1.

[0123] Comparative Example 3 An electrolyte precursor and an amorphous solid electrolyte were obtained in the same manner as in Comparative Example 1, except that the circulation stirring time was changed to 72 hours. The amount of Li2S remaining in the obtained amorphous solid electrolyte was calculated in the same manner as in Example 1. The results are shown in Table 1.

[0124] Comparative Example 4 An electrolyte precursor and an amorphous solid electrolyte were obtained in the same manner as in Comparative Example 1, except that the circulation stirring time was changed to 140 hours. The amount of Li2S remaining in the obtained amorphous solid electrolyte was calculated in the same manner as in Example 1. The results are shown in Table 1.

[0125] Comparative Example 5 An electrolyte precursor and an amorphous solid electrolyte were obtained in the same manner as in Comparative Example 1, except that the circulation stirring time was set to 300 hours. The amount of Li2S remaining in the obtained amorphous solid electrolyte was calculated in the same manner as in Example 1. The results are shown in Table 1. In addition, the obtained crystalline solid electrolyte was subjected to powder X-ray diffraction (XRD) measurement and ionic conductivity measurement in the same manner as in Example 1. The results are shown in FIG. 6 and Table 1.

[0126] Comparative Example 6 In a Schlenk flask (volume: 100 mL) with a stirrer, 1.17 g of lithium sulfide (Li2S), 1.89 g of diphosphorus pentasulfide (P2S5), 0.37 g of lithium bromide (LiBr), and 0.57 g of lithium iodide (LiI) were introduced under a nitrogen atmosphere. After rotating the stirrer, 40 mL of cyclohexane was added, followed by 4.1 mL of THF. The solids in the slurry settled and flocculated, causing poor stirring and making it difficult to continue stirring.

[0127] Comparative Example 7 The same procedure as in Comparative Example 6 was carried out except that 1.8 mL of DME was used instead of THF. As a result, the solids in the slurry settled and aggregated, resulting in poor stirring and making it difficult to continue stirring.

[0128] [Table 1] *1. Molar ratio to Li3PS4. *2, DME (dimethoxyethane) *3, EA (Ethyl acetate) [Industrial Applicability]

[0129] According to the method for producing a solid electrolyte of the present embodiment, a crystalline solid electrolyte having high ionic conductivity can be produced. The crystalline solid electrolyte obtained by the method for producing a solid electrolyte of the present embodiment is suitable for use in batteries, particularly batteries used in information-related devices and communication devices such as personal computers, video cameras, and mobile phones.

Claims

1. A method for producing a solid electrolyte, comprising: a first step of mixing two or more compounds satisfying the following (1) and a complexing agent 1 satisfying the following (2); and, after the first step, a second step of further mixing a complexing agent 2 satisfying the following (3). (1) A compound containing at least one element selected from the group consisting of lithium, sulfur, phosphorus and halogen elements. (2) Li 3 P.S. 4 and a complexing agent capable of forming a complex containing a halogen element. (3) Li 3 P.S. 4 A complexing agent other than complexing agent 1 capable of forming a complex comprising:

2. The method for producing a solid electrolyte according to claim 1 , wherein the complexing agent 1 contains a nitrogen element.

3. The method for producing a solid electrolyte according to claim 1 or 2, wherein the complexing agent 2 contains an oxygen element.

4. The method for producing a solid electrolyte according to any one of claims 1 to 3, wherein the complexing agent 1 has two or more amino groups.

5. The method for producing a solid electrolyte according to any one of claims 1 to 4, wherein the complexing agent 2 has one or more groups selected from the group consisting of an ether group and an ester group.

6. The method for producing a solid electrolyte according to any one of claims 1 to 5, wherein the complexing agent 1 is tetramethylethylenediamine.

7. The method for producing a solid electrolyte according to any one of claims 1 to 6, wherein the complexing agent 2 is tetrahydrofuran.

8. The method for producing a solid electrolyte according to any one of claims 1 to 6, wherein the complexing agent 2 is dimethoxyethane.

9. The method for producing a solid electrolyte according to any one of claims 1 to 8, wherein a molar ratio of the amount of complexing agent 1 added to a total molar amount of Li atoms contained in two or more of the compounds satisfying the condition (1) is 0.1 or more and 2.0 or less.

10. Li that can be produced from two or more compounds that satisfy the above (1) 3 P.S. 4 The method for producing a solid electrolyte according to any one of claims 1 to 9, wherein a molar ratio of the amount of complexing agent 2 added to the total molar amount of is 1.0 or more and 5.0 or less.

11. The method for producing a solid electrolyte according to any one of claims 1 to 10, wherein the compound satisfying (1) includes a lithium halide.

12. The method for producing a solid electrolyte according to any one of claims 1 to 11, wherein the compound satisfying (1) contains an elemental halogen.

13. The method for producing a solid electrolyte according to any one of claims 1 to 12, wherein the halogen element is a bromine element and an iodine element.

14. The method for producing a solid electrolyte according to any one of claims 1 to 13, wherein the compound satisfying (1) includes lithium sulfide and diphosphorus pentasulfide.

15. The compound satisfying the above (1) is Li 3 P.S. 4 The method for producing the solid electrolyte according to any one of claims 1 to 14, comprising:

16. The method for producing a solid electrolyte according to any one of claims 1 to 15, wherein pulverization and mixing is not performed in the first step.

17. The method for producing a solid electrolyte according to any one of claims 1 to 16, wherein the solid electrolyte comprises a thiolicon region II type crystal structure.

18. The method for producing a solid electrolyte according to any one of claims 1 to 17, wherein the solid electrolyte does not have diffraction peaks at 2θ = 17.5 ° and 26.1 ° in X-ray diffraction measurement using CuKα rays.

Citation Information

Patent Citations

  • Liquid solution for formation of a solid electrolyte-containing layer of all-solid type lithium secondary battery, all-solid type lithium secondary battery, and method for manufacturing the same

    JP2014191899A

  • Production method of solid electrolyte

    WO2014192309A1

  • Method for producing solid electrolyte

    WO2017159666A1

  • Solid electrolyte and method for producing solid electrolyte

    WO2017159667A1

  • Solid lithium electrolytes and process of production

    WO2018054709A1